A Century of Grading Research: Meaning and Value in the Most Common Educational Measure. (December 2016) - Brookhart, Susan M.; Guskey, Thomas R.; Bowers, Alex J.; McMillan, James H.; Smith, Jeffrey K.; Smith, Lisa F.; Stevens, Michael T.; Welsh, Megan E.
Grading refers to the symbols assigned to individual pieces of student work or to composite measures of student performance on report cards. This review of over 100 years of research on grading considers five types of studies: (a) early studies of the reliability of grades, (b) quantitative studies of the composition of K–12 report card grades, (c) survey and interview studies of teachers' perceptions of grades, (d) studies of standards-based grading, and (e) grading in higher education. Early 20th-century studies generally condemned teachers' grades as unreliable. More recent studies of the relationships of grades to tested achievement and survey studies of teachers' grading practices and beliefs suggest that grades assess a multidimensional construct containing both cognitive and noncognitive factors reflecting what teachers value in student work. Implications for future research and for grading practices are discussed.